The glycan shield of HIV is predominantly oligomannose independently of production system or viral clade. - Bonomelli, C; Doores, K; Dunlop, D; Thaney, V; Dwek, R; Burton, D; Crispin, M; Scanlan, C (Public Library of Science, 2011)
The N-linked oligomannose glycans of HIV gp120 are a target for both microbicide and vaccine design. The extent of cross-clade conservation of HIV oligomannose glycans is therefore a critical consideration for the development of HIV prophylaxes. We measured the oligomannose content of virion-associated gp120 from primary virus from PBMCs for a range of viral isolates and showed cross-clade elevation (62-79%) of these glycans relative to recombinant, monomeric gp120 (~30%). We also confirmed that pseudoviral production systems can give rise to notably elevated gp120 oligomannose levels (~98%), compared to gp120 derived from a single-plasmid viral system using the HIV(LAI) backbone (56%). This study highlights differences in glycosylation between virion-associated and recombinant gp120.